A moldable thermosensitive hydroxypropyl chitin hydrogel for 3D cartilage regeneration in vitro and in vivo. (May 2020) - Xu, Yawen; Xu, Yong; Bi, Bo; Hou, Mengjie; Yao, Lin; Du, Qiran; He, Aijuan; Liu, Yu; Miao, Chunlei; Liang, Xiaoqin; Jiang, Xulin; Zhou, Guangdong; et al.
Abstract: Because of poor self-repair capacity, the repair of cartilage defect is always a great challenge in clinical treatment. In vitro cartilage regeneration provides a potential strategy for functional reconstruction of cartilage defect. Hydrogel has been known as an ideal cartilage regeneration scaffold. However, to date, in vitro cartilage regeneration based on hydrogel has not achieved satisfactory results. The current study explored the feasibility of in vitro 3D cartilage regeneration based on a moldable thermosensitive hydroxypropyl chitin (HPCH) hydrogel and its in vivo fate. The thermosensitive HPCH hydrogel was prepared and characterized. Goat auricular chondrocytes were encapsulated into the HPCH hydrogel to form a chondrocyte-hydrogel construct. The constructs were injected subcutaneously into nude mice or molded into different shapes for in vitro chondrogenic culture followed by in vivo implantation. The results demonstrated that the HPCH hydrogel possessed satisfactory gelation properties (gelation time < 18 s at 37 °C), biocompatibility (cell amount almost doubled within one week), and the ability to be applied as an injectable hydrogel for cartilage regeneration. All the constructs of in vitro culture basically maintained their original shapes ( in vitro to initial: 110.8%) and displayed typical cartilaginous features with abundant lacunae and cartilage specific matrix deposition. These in vitro samples became more mature with prolonged in vivo implantation and largely maintained the original shape ( in vivo to in vitro : 103.5%). These results suggested that the moldable thermosensitive HPCH hydrogel can serve as a promising scaffold for cartilage regeneration with defined shapes in vitro and in vivo. Statement of significance: Because of avascular and non-nervous characteristic of cartilage, in vitro regeneration plays an important role in reconstructing cartilage function. Hydrogel has been known as an ideal cartilage regeneration scaffold. However, to date, in vitro cartilage regeneration based on hydrogel has not achieved satisfactory results. The current study demonstrated that the chondrocyte-hydrogel construct generated by high density of chondrocytes encapsulated into a thermosensitive HPCH hydrogel could successfully regenerate in vitro typical cartilage-like tissue with defined shapes and further mature to form homogeneous cartilage with their original shapes after in vivo implantation. The current study indicated that the moldable thermosensitive HPCH hydrogel could serve as a promising scaffold for in vitro and in vivo cartilage regeneration with different shapes. Graphical abstract: Image, graphical abstract